2022
DOI: 10.3390/agronomy12061335
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Control and Biochemical Characteristics of Giant Hogweed (Heracleum sosnowskyi Manden.) Treated with Microwaves

Abstract: There is an urgent need to develop new compensatory and human-safe methods for controlling invasive Heracleum species. This research aimed to determine the effectiveness of H. sosnowskyi control under microwave radiation and biochemical changes in tissues and sap after irradiation. In field experiments in southern Poland, the plants were cut and irradiated with a device generating electromagnetic waves (2.45 GHz, 32.8 kW/m2). The control efficacy of plants in the rosette phase irradiated for 5, 10, or 15 min w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…So far, the MV control technique has been used against another invasive species—Sosnowski hogweed ( Heracleum Sosnowskyi Manden. )—also after the prior cutting of aboveground biomass and exposure of plants to MV with a frequency of 2.45 GHz and a power density of 30.0 kW/m 2 emitted by the tubular antenna [ 28 ]. In the case of Sosnowski hogweed, 10 min of MV was enough to destroy the plants and effectively prevent their further regrowth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…So far, the MV control technique has been used against another invasive species—Sosnowski hogweed ( Heracleum Sosnowskyi Manden. )—also after the prior cutting of aboveground biomass and exposure of plants to MV with a frequency of 2.45 GHz and a power density of 30.0 kW/m 2 emitted by the tubular antenna [ 28 ]. In the case of Sosnowski hogweed, 10 min of MV was enough to destroy the plants and effectively prevent their further regrowth.…”
Section: Discussionmentioning
confidence: 99%
“…In our research, the shoots’ temperature and the substrate’s surrounding surface increased to 85–90 °C after 20.0–25.0 min of MV exposure. At such a high temperature, irreversible biochemical changes occur in plant tissues, i.e., denaturation of proteins and changes in their composition, changes in the composition of carbohydrates, and significant changes in the metabolism of amino acids and the glyoxylate and galactose pathways, which was observed after the use of MV in tissues of Sosnowski hogweed [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that a single 10 min treatment with microwaves at 2.45 GHz can prevent regrowth of invasive hogweed (Heracleum sp.) for an entire season [23].…”
Section: Introductionmentioning
confidence: 99%